2015
DOI: 10.1016/j.prevetmed.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for visible lesions or positive laboratory tests in bovine tuberculosis reactor cattle in Northern Ireland

Abstract: An observational case-control study was conducted to investigate risk factors for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 39 publications
(35 reference statements)
2
40
3
1
Order By: Relevance
“…However, our findings are not directly comparable with O'Hagan et al (2015), as for our animals to survive within our cohort to older ageclasses, they have to remain SCITT negative throughout their life, but gaining potential time at risk. All animals studied in O'Hagan et al (2015) were SCITT reactors, which would have been culled at the point of detection. Therefore, it is possible that the two studies focus on differing cohorts, each with potentially differing selective pressures.…”
Section: Accepted Manuscriptcontrasting
confidence: 65%
See 3 more Smart Citations
“…However, our findings are not directly comparable with O'Hagan et al (2015), as for our animals to survive within our cohort to older ageclasses, they have to remain SCITT negative throughout their life, but gaining potential time at risk. All animals studied in O'Hagan et al (2015) were SCITT reactors, which would have been culled at the point of detection. Therefore, it is possible that the two studies focus on differing cohorts, each with potentially differing selective pressures.…”
Section: Accepted Manuscriptcontrasting
confidence: 65%
“…O'Hagan et al (2015) found that for reactor animals in NI there was reduced risk of having bTB confirmed with increasing age (O'Hagan et al, 2015). However, our findings are not directly comparable with O'Hagan et al (2015), as for our animals to survive within our cohort to older ageclasses, they have to remain SCITT negative throughout their life, but gaining potential time at risk. All animals studied in O'Hagan et al (2015) were SCITT reactors, which would have been culled at the point of detection.…”
Section: Accepted Manuscriptcontrasting
confidence: 51%
See 2 more Smart Citations
“…Co‐factors investigated in our models are presented in Table . We hypothesized that these variables could be influential in the antemortem test variability, confirmation or pathology, and previous research suggested that they may be important (e.g., Humblet, Boschiroli, & Saegerman, ; O'Hagan et al., ; Broughan et al., ; Downs et al., ; Shittu, Clifton‐Hadley, Ely, Upton, & Downs, ). We generated two variables to capture the movement histories of animals over their lifetime: (i) the number of herds an animal was recorded residing within over its lifetime (LOG_NUM_HERDS) and (ii) the total number of trade moves (known as market moves within the APHIS data set; LIFETIME_MARKET_MOVES) recorded for an animal over its life.…”
Section: Methodsmentioning
confidence: 99%